A cross-sectional study evaluating tick-borne encephalitis vaccine uptake and timeliness among adults in Switzerland. - Kyra D Zens; Vasiliki Baroutsou; Philipp Sinniger; Phung Lang (PLoS ONE)
The goal of this study was to evaluate timeliness of Tick-borne Encephalitis vaccination uptake among adults in Switzerland. In this cross-sectional survey, we collected vaccination records from randomly selected adults 18-79 throughout Switzerland. Of 4,626 participants, data from individuals receiving at least 1 TBE vaccination (n = 1875) were evaluated. We determined year and age of first vaccination and vaccine compliance, evaluating dose timeliness. Participants were considered "on time" if they received doses according to the recommended schedule ± a 15% tolerance period. 45% of participants received their first TBE vaccination between 2006 and 2009, which corresponds to a 2006 change in the official recommendation for TBE vaccination in Switzerland. 25% were first vaccinated aged 50+ (mean age 37). More than 95% of individuals receiving the first dose also received the second; ~85% of those receiving the second dose received the third. For individuals completing the primary series, 30% received 3 doses of Encepur, 58% received 3 doses of FSME-Immun, and 12% received a combination. According to "conventional" schedules, 88% and 79% of individuals received their second and third doses "on time", respectively. 20% of individuals receiving Encepur received their third dose "too early". Of individuals completing primary vaccination, 19% were overdue for a booster. Among the 31% of subjects receiving a booster, mean time to first booster was 7.1 years. We estimate that a quarter of adults in Switzerland were first vaccinated for TBE aged 50+. Approximately 80% of participants receiving at least one vaccine dose completed the primary series. We further estimate that 66% of individuals completing the TBE vaccination primary series did so with a single vaccine type and adhered to the recommended schedule.